The Phenomenon of Artificial Intelligence-Based Photo Manipulation: A Thematic Hadith Analysis of Tashwir - Zahrani Camelia Bilqis; Mohammad Kurnaini (Hikmah, 2026)
Advances in Artificial Intelligence (AI) technology, particularly deepfakes and Generative Adversarial Networks (GANs), have given rise to the phenomenon of photo manipulation capable of producing ultra-realistic images of living beings. This phenomenon raises new issues in contemporary hadith studies regarding the legal status of AI-based photo manipulation from the perspective of tashwir. This study aims to analyze the legal status of AI-based photo manipulation through a thematic hadith analysis approach (tahlil maudhu’i). The research employs a qualitative, literature-based method (library research), with primary sources consisting of hadiths on tashwir found in Sahih al-Bukhari and Sahih Muslim. Data were collected through hadith takhrij, documentary studies, and analysis of the opinions of classical and contemporary scholars. The results of the study reveal four main themes: al-mudhahah bi khalqillah, the context and purpose of use, al-shidq wa tahrim al-tadlis, and rukhsah. The study concludes that the ruling on AI-based photo manipulation is contextual. Manipulation that realistically produces a new image or contains elements of deception is deemed haram, whereas technical manipulation that does not alter the identity of the object and is performed for a specific benefit may be permitted under certain conditions.